A survey on potato productivity, cultivation and management constraints in Mbala district of Northern Zambia - Chilipa Lorraine N. K. (De Gruyter, 2021)
In Zambia, potato (Solanum tuberosum L.) cultivation is ranked the third most important among root and tuber crops after cassava (Manihot esculenta Crantz) and sweet potato (Ipomoea batatas (L.) Lam.). In spite of its importance, the productivity and cultivation of potato remain low. In the light of this, a survey was conducted in Mbala district to obtain and document farmers’ knowledge on potato cultivation and understand the constraints associated with potato cultivation and management. Four agricultural camps in Mbala district were purposefully sampled due to the high potato cultivation activity. Data were collected from 116 potato farmers through structured questionnaires and focus group discussions. Results showed that three major constraints in potato cultivation were white grub (Phyllophaga spp.), foliar wilts (Ralstonia spp. and Verticillium spp.) and seed source, with a farmer-ranked mean-derived score of 3.75, 3.5 and 2.75, respectively. Farmers ascribed 70% crop damage to white grub (Phyllophaga spp.) and 60% crop damage to foliar wilts (Ralstonia spp. and Verticillium spp.). Other information obtained indicated that the majority of the farmers (>85%) were married, above 35 years and had at least primary education. The majority of the farmers involved in the study had less than 0.25 ha under potato production. To reduce the cultivation constraints for increased potato production in Mbala, direct breeding efforts, potato crop protection and other measures need to be employed.